Menstrual hygiene management in flood-affected Bangladesh: addressing socio-cultural barriers, infrastructure gaps, and policy responses - Al-Mamun, Md.; Kalam, Abul; Karim, Md. Zawadul; Alam, Marufa; Khan, Tauhid Hossain (Frontiers in Public Health, 2025)
Women and adolescent girls in flood-prone regions of Bangladesh face significant challenges in managing menstrual hygiene, which severely impacts their health, dignity, and well-being. This study investigates the socio-cultural, infrastructural, and policy barriers to menstrual hygiene management (MHM) during floods in the districts of Noakhali, Feni, Barisal, Khulna, and Satkhira. Conducted from June to October 2024, the research employed a purposive sampling approach, with 30 in-depth interviews (IDIs) conducted with women and adolescent girls directly affected by the floods. Additionally, 12 key informant interviews (KIIs) were carried out with healthcare workers, NGO representatives, and policymakers, alongside field observations in temporary shelters and relief centers. The findings highlight critical barriers, including the lack of accessible and private sanitation facilities in shelters, compounded by inadequate supplies of menstrual hygiene products. In temporary shelters, the absence of specialized toilets and waste disposal systems for menstruation forces women to resort to unhygienic alternatives such as cloth, leaves, or newspapers, leading to increased health risks. Socio-cultural taboos surrounding menstruation further restrict access to proper hygiene materials and support, intensifying the challenges. Moreover, disaster management systems fail to incorporate menstrual hygiene needs, leaving women and girls particularly vulnerable during floods. The study recommends integrating gender-responsive disaster management policies and comprehensive menstrual health education into disaster relief efforts. The Minimum Initial Service Package (MISP) should be utilized to provide urgent reproductive health services. These findings are crucial for policymakers, healthcare professionals, and researchers, and underscore the importance of reducing stigma and promoting dignity for women and girls. By addressing these gaps, Bangladesh can enhance the resilience and health of women and adolescent girls in the aftermath of floods.